ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN IMPLEMENTASI PROGRAM PIS-PK DI PUSKESMAS GADING PADANG LAWAS TAHUN 2020 - rini yunika andalia (Jurnal Inovasi Kesehatan Masyarakat, 2020)
Policy implementation is a way for a policy to achieve its objectives. The implementation of this policy is the Healthy Indonesia Program with a Family Approach. In implementing the healthy indonesia program family approach policy there are related factors, namely knowledge, attitudes, communication, bureaucratic structure. Study was to determine the Factors Associated with the healthy indonesia program family approach in Gading Padang Lawas Health Center in 2020. The type of study is quantitative study with cross sectional approach that independent variables with the dependent variable faced by community health center staff in implementing the healthy indonesia program family approach in the work area of ​​the Ivory Law Center in Padang Lawas in 2020. The population of this study is all family heads registered in the community health center in Gading Padang Lawas totaling 115 people. a sample of 57 people using a questionnaire. The results obtained by variables related to healthy indonesia program family approach Policy Implementation are: knowledge (p value = 0,000), attitude (p value = 0,000), communication (p value = 0,000), bureaucratic structure (p value = 0.002). It is recommended for respondents to increase healthy clean living behavior on themselves and be diligent to check themselves to the nearest health center when sick